Kapabilitas Dinas Perikanan Dan Ketahanan Pangan Dalam Pemberdayaan Kelompok Budidaya Ikandi Kabupaten Kuantan Singingi - Windri Wardani; Rahyunir Rauf (UIR Press, 2020)
The Department of Fisheries and Food Security has a function in empowering fish breeders in Kuantan Singingi Regency. To carry out these functions, 20 types of activities have been determined as stated in the work plan in 2019. The research objective is to determine and analyze the Capability of the Fisheries Service and Food Security in EmpoweringFish Cultivation Groups in Kuantan Singingi Regency and to provide problem solving. Capability of the Fisheries Service and Internal Food Security. Empowerment of Fish Cultivation Groups in Kuantan Singingi Regency. This type of research is a descriptive survey using qualitative methods. Data were obtained from research informants who were determined bymeans of the informant determination technique using snowball sampling. Data collection was carried out by means ofinterviews, observation, and documentation, then all data collected was carried out by data validation steps and then analyzed one by one so that the research results could be drawn in the form of conclusions. The results of the study found that the capability of the Fisheries and Food Security Office of Kuantan Singingi Regency in empowering fish farming groups has been carried out with human resources, existing policies, predetermined budget allocations, and the existence of empowerment techniques that have been established every year. In the Capability of the Department of Fisheries and Food Security of Kuantan Singingi Regency in empowering fish farming groups, there are several obstacles in the form ofa lack of human resources and limited budget funds allocated for implementing programs in the aquaculture sector.